Identification of Conformational Antigenic Epitopes and Dominant Amino Acids of Buffalo β‐Lactoglobulin. Issue 4 (1st April 2014) - Xin, Li; Jinyan, Gao; Shengfa, He; Yuanyuan, Wu; Hongbing, Chen
Abstract Major allergen β‐lactoglobulin exists in many mammalian types of milk except human breast. Buffalo milk also contains this major allergen but the detailed information on its epitopes is not available. The aim of this work was to map and characterize its conformational antigenic epitopes. Sixty mimotopes of buffalo β‐lactoglobulin were produced by biopanning of phage display peptide library and then 2 mimotopes, specific for sera from rabbit 1 and 2, respectively, were predicted to be conformational epitope candidates by the use of DNAStar and web tool of MIMOX. On the basis of bioinformation analysis, 5 conserved amino acid residues PL‐ENK were identified in 2 conformational epitope sequences and 7 conformational epitopes were derived from 2 mimotopes by molecular modeling. The result showed that these conformational epitopes were located in the 2 regions on buffalo β‐lactoglobulin and composed of 5 hydrophilic and 2 hydrophobic amino acids.